2014
DOI: 10.1097/gme.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine biomarkers and symptom clusters during the menopausal transition and early postmenopause

Abstract: Objective During the menopausal transition and early postmenopause participants in the Seattle Midlife Women's Health Study (SMWHS) were likely to belong to one of three symptom severity classes: severe hot flashes with moderate sleep, mood, cognitive, and pain symptoms (High-severity Hot Flash); moderate levels of all but hot flashes (Moderate Severity); and low levels of all (Low Severity). We tested models of differential effects of hypothalamic-pituitary-ovarian (HPO), hypothalamic-pituitary-adrenal (HPA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…Woods and colleagues found that levels of urinary estrone, FSH, epinephrine, and norepinephrine differentiated the three symptoms clusters identified in their earlier analyses. 1,2 Women in a cluster including severe hot flashes had higher overnight norepinephrine and FSH levels and lower estrone and epinephrine levels than those with low severity symptoms. 2 In addition women’s progression through the menopausal transition stages to the late menopausal transition and early postmenopause resulted in a greater likelihood of a symptom cluster with high severity hot flashes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Woods and colleagues found that levels of urinary estrone, FSH, epinephrine, and norepinephrine differentiated the three symptoms clusters identified in their earlier analyses. 1,2 Women in a cluster including severe hot flashes had higher overnight norepinephrine and FSH levels and lower estrone and epinephrine levels than those with low severity symptoms. 2 In addition women’s progression through the menopausal transition stages to the late menopausal transition and early postmenopause resulted in a greater likelihood of a symptom cluster with high severity hot flashes.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition, higher FSH, lower estrone, higher norepinephrine and lower epinephrine levels were associated with cluster 1. 2 …”
mentioning
confidence: 99%
“…For example, we found that the symptom cluster in which hot flash was the most severe and dominant symptom was related to having lower levels of urinary estrone, higher levels of follicle stimulating hormone, lower epinephrine, and higher norepinephrine levels, suggesting that this cluster of symptoms may be mediated by both ovarian steroids and the autonomic nervous system. 6 This same cluster was more likely to occur during the late menopausal transition and early postmenopause, and was associated with a variant in the 17 hydroxysteroid dehydrogenase (HSD) gene polymorphism, as well as higher levels of stress, than observed in the low-symptom-severity cluster (unpublished data).…”
mentioning
confidence: 89%
“…For example, when using LCA for symptom clusters, LCA identifies groups of people who have a similar symptom experience. LCA has been successfully used to determine symptom cluster membership in various patient populations including myocardial infarction 15 , cancer 16,17 , and the menopause transition 18 …”
Section: Conceptual Views Of Symptom Clustersmentioning
confidence: 99%